Staying curious: why lifelong learning matters - Hashim, Hazwati (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Lifelong learning is the continuous acquisition of knowledge, skills, and competencies throughout life, driven by curiosity and essential for personal, social, and professional growth. It sustains cognitive health, as studies show that later-life learning preserves mental clarity, fluid intelligence, and reduces dementia risk, while also being influenced by social and cultural contexts (Wang et al., 2025; Takeuchi et al., 2023; Merriam & Mohamad, 2000). Additionally, lifelong learning enhances personal growth and well-being, boosting motivation, self-confidence, optimism, and social integration, as seen in language learning and other educational activities (Abiddin, 2023; Van der Ploeg, 2023).